The Role of the City Government and the Private Sector in Shaping the Face of South Tangerang City in the Future: An Analysis of Scenario Planning - Damar Wijanarko; Reza Fathurrahman (Publikasi Indonesia, 2024)
The city of South Tangerang, located in the south of DKI Jakarta, plays a role as a buffer city with a very strategic location. The city attracts many individuals and corporations to live, do business, and invest thanks to its potential and attractiveness. Tangerang has grown rapidly in less than two decades, much of which has also been supported by large private investors and developers such as Jaya, Sinar Mas, Lippo, and Ciputra. Therefore, synergy between the City Government and the private sector is very important in the development and development of the city. Amid change and uncertainty, scenario planning analysis methods are applied to formulate various public policies that support urban development goals by considering internal and external risks. This policy paper discusses the possibility of the future of Tangerang City based on efforts and harmony between the City Government and the private sector.